India: the giant awakens! - Sonalker, Manoher V. (New Delhi : Atlantic Pub., 2007)
India is slowly awakening from the sleep extending over half a century and gradually taking its rightful place in the country of nations. Gone are the days when agrarian economy characterized the Indian economy. Today, industrial and services sectors are playing important role in the country,s economy. While fast development is perceptible in these sectors, considerable progress has also been made in the agricultural sector owing to the green revolution. Consequently, there has been a marked increase in the national income since Independence. But will it be correct to say that India has succeeded in providing all its citizens a better quality of life? has it built up a nation where even the poorest citizen can lead a life of simple dignity with at least his basic needs being satisfied? Has it been able to ensure that not a single citizen will remain hungry even for a day? has it guaranteed an affordable shelter to all, and access to education to all its citizens? Has it instilled the spirit of unity and oneness among the millions of citizens of diverse caste, creed, community, religion or state? has the government policy brought a significant improvement in the general lot or the people are still striving for their socio-economic rights? Numerous questions need to be answered to realise the steady progress of India in diverse fields in true spirit.
Keywords: India-pre Independence era; India-post Independece development